Investigation of filler material to the corrosion behaviour of aluminium alloys weldment - Abdul Rahim, Mohamed (2012)
The thesis present the effect of filler material to the corrosion behavior of AA6061 alluminum alloys welded joint. Study were made to observe the effect of filler material type ER4043, ER047 and the increment of welding current, 30 A, 35 A, and 40 A on corrosion rate of welded AA6061 joints. Welding was done by using Tungsten Inert Gas (TIG) welding and corrosion test was conducted in a lab using potentiostat. From the experiment, specimens with the highest corrosion rate is specimen 4 with the value of corrosion rate 2.88 mmpy and specimen with the lowest value of corrosion rate is specimen 3 with the value as low as 0.32828 mmpy. As the conclusion, filler material type ER4043 increase corrosion resistance on the welding joint and current 40 A is better in order the heighten the corrosion resistance of the material.